2022
DOI: 10.21203/rs.3.rs-1479303/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

PET Imaging of the cannabinoid receptor type 2 in humans using [11C]MDTC

Abstract: Purpose: We report findings from the first-in-human study of [ 11 C]MDTC, a radiotracer developed to image the cannabinoid receptor type 2 (CB2R) with positron emission tomography (PET). Methods: Ten healthy adults were imaged according to a 90 min dynamic PET protocol after bolus intravenous injection of [ 11 C]MDTC. Five participants also completed a second [ 11 C]MDTC PET scan to assess test-retest reproducibility of receptor-binding outcomes. The kinetic behavior of [ 11 C]MDTC in human brain was evaluated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…37 Recently, Du et al reported the first-in-human study of [ 11 C]A836339 in healthy subjects. 38,39 The radiotracer displayed promising pharmacokinetic properties, supporting further studies in conditions with hCB2 upregulation. 38,39 To date, no ideal CB2 PET-radioligand has been characterized in the clinical setting.…”
Section: ■ Introductionmentioning
confidence: 56%
See 1 more Smart Citation
“…37 Recently, Du et al reported the first-in-human study of [ 11 C]A836339 in healthy subjects. 38,39 The radiotracer displayed promising pharmacokinetic properties, supporting further studies in conditions with hCB2 upregulation. 38,39 To date, no ideal CB2 PET-radioligand has been characterized in the clinical setting.…”
Section: ■ Introductionmentioning
confidence: 56%
“…2-Oxoquinoline [ 11 C]­NE40 was evaluated in healthy volunteers and AD patients, however the tracer failed to show colocalized binding in the area of Aβ-plaques (Figure A) . Recently, Du et al reported the first-in-human study of [ 11 C]­A836339 in healthy subjects. , The radiotracer displayed promising pharmacokinetic properties, supporting further studies in conditions with hCB2 upregulation. , To date, no ideal CB2 PET-radioligand has been characterized in the clinical setting.…”
Section: Introductionmentioning
confidence: 96%
“…As discussed in this review, innovations continue in 11 C-radiolabelling strategies for applications in 11 C-tracer development. Within the past five years, to our knowledge at least 27 novel 11 C-labelled PET tracers have been translated for FIH PET studies (see Figure 1 ) [ 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 , 103 , 104 , 105 , 106 , 107 , 108 , 109 ]. Unsurprisingly, the vast majority of these PET tracers were designed to image targets within the CNS (see Table 1 ).…”
Section: First-in-human Translationmentioning
confidence: 99%
“…Several CB 2 R ligands have been developed and evaluated (Ni et al, 2019b), including [ 11 C]NE40 (Vandeputte et al, 2012), [ 11 C]A-836339 (MDTC) (Pottier et al, 2017;Du et al, 2022), [ 18 F]MA3 (Attili et al, 2019), [ 18 F]FC0324 (Caillé et al, 2017), [ 18 F]JHU94620 (Moldovan et al, 2016), [ 18 F]LU13 (Gündel et al, 2022), [ 18 F]DM102 (Modemann et al, 2022), [ 18 F]CRA13 (Hassan et al, 2020), [ 11 C]RS-016 (Meletta et al, 2017), [ 11 C]RS-028 (Haider et al, 2018), [ 11 C]RSR-056 (Slavik et al, 2015), and [ 18 F]RoSMA-18-d6 (Haider et al, 2020). Thus far, only one in-human in vivo CB 2 R PET using [ 11 C]NE40 (Ahmad et al, 2016) in patients with AD and healthy controls has been reported, showing no group difference.…”
Section: Introductionmentioning
confidence: 99%